Rock-Sourced Nitrogen in Semi-Arid, Shale-Derived California Soils - Bingham, Nina L.; Slessarev, Eric W.; Homyak, Peter M.; Chadwick, Oliver A. (Frontiers in Forests and Global Change, 2021)
Models suggest that rock-derived nitrogen (N) inputs are of global importance to ecosystem N budgets; however, field studies demonstrating the significance of rock N inputs are rare. We examined rock-derived N fluxes in soils derived from sedimentary rocks along a catena formed under a semi-arid climate. Our measurements demonstrate that there are distinct and traceable pools of N in the soil and bedrock and that the fraction of rock-derived N declines downslope along the catena. We used geochemical mass balance weathering flux measurements to estimate a rock-derived N flux of 0.145 to 0.896 kg ha-1 yr-1 at the ridgecrest. We also developed independent N flux estimates using a 15N-based isotope mixing model. While geochemical mass-balance-based estimates fell within the 95% confidence range derived from the isotope mixing model (-1.1 to 44.3 kg ha-1 yr-1), this range was large due to uncertainty in values for atmospheric 15N deposition. Along the catena, N isotopes suggest a diminishing effect of rock-derived N downslope. Overall, we found that despite relatively large N pools within the saprolite and bedrock, slow chemical weathering and landscape denudation limit the influence of rock-derived N, letting atmospheric N deposition (7.1 kg ha-1 yr-1) and N fixation (0.9-3.1 kg ha-1 yr-1) dominate N inputs to this grassland ecosystem.